SOCIODEMOGRAPHIC AND HEALTHCARE FACTORS AS DETERMINANTS OF CHILDHOOD BASIC IMMUNIZATION INCOMPLETION IN PAPUA: Faktor Sosiodemografi dan Layanan Kesehatan sebagai Determinan Ketidaklengkapan Imunisasi Dasar Anak di Provinsi Papua - Ika Puspita Asturiningtyas; Sri Nuryani Wahyuningrum (Universitas Airlangga, 2023)
Background: The morbidity and mortality rate for children under five in Indonesia is high in eastern Indonesia. Incomplete coverage of basic immunization for children under five can increase the risk of Vaccine-Preventable Diseases (VPD). As a province in eastern Indonesia, the coverage of complete basic immunization in Papua is low. Purpose: This study aimed to identify sociodemographic and healthcare factors among children who default to complete basic immunizations in Papua. Methods: This study utilized data from the 2018 Indonesian National Basic Health Research (Riskesdas). The sample was children aged 12-35 months who live in the Census Blocks (BS) of Riskesdas 2018 in Papua Province and selected to be the sample of Riskesdas 2018. Totally 453 children were included. Bivariate analysis of the data was using Chi-Square test and multivariate with logistic regression. Results: The result showed that the prevalence rate for defaulting basic immunization was 71.74%. Sociodemographic factors that increased incomplete basic immunization were poor economic families (OR=1.97; 95% CI=1.10-3.56) and low maternal education (OR=2.00; 95%CI=1.09-3.65). Meanwhile, healthcare factors like no immunization card (OR=6.82; 95%CI=2.65-17.56) and not being born in a healthcare facility (OR=6.05; 95%CI=3.14-11.66) become the strongest factors that increase the risk of incomplete basic immunization. Conclusion: This study indicates that sociodemographic and healthcare factors could increase the risk of incomplete basic immunization in Papua. It is important to actively improve healthcare services and educate people about the importance of immunization to reduce the risk of incomplete basic immunization for children in Papua.